2016
DOI: 10.1371/journal.pone.0152696
|View full text |Cite
|
Sign up to set email alerts
|

Dry Eye Disease in Patients with Functioning Filtering Blebs after Trabeculectomy

Abstract: PurposeThe aim of this study was to analyze dry eye disease (DED) in patients with functioning filtering blebs and to explore the relationship between the morphology of filtering blebs and ocular surface instability.MethodsThis was a cross-sectional, case-comparison study. Seventy glaucomatous patients (70 eyes) with functioning blebs who had undergone trabeculectomy more than 6 months prior (study group) and 35 control subjects (35 eyes) (control group) were included. All subjects completed an ocular symptom … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 34 publications
0
23
0
Order By: Relevance
“…This seems in accordance with our study, that considered early to moderate glaucoma. In a different study, Ji and coworkers reported that 40% of patients with functioning filtering blebs suffered from symptomatic dry eye, with higher CFS scores and lower BUT values 16 . Interestingly, the occurrence of dry eye significantly correlated with the bleb features, being higher in patients with elevated and microcystic blebs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This seems in accordance with our study, that considered early to moderate glaucoma. In a different study, Ji and coworkers reported that 40% of patients with functioning filtering blebs suffered from symptomatic dry eye, with higher CFS scores and lower BUT values 16 . Interestingly, the occurrence of dry eye significantly correlated with the bleb features, being higher in patients with elevated and microcystic blebs.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, as stated above, other factors must be considered when interpreting the post-surgical OS system changes. (i) The mechanical effects of the new-formed filtration bleb may disturb the tear film stability, and induce a persistency of a significant form of dry eye 16,17,27,28 . (ii) The use of intra-operative MMC induces toxic effects on the OS system, by inhibiting the proliferation of corneal and conjunctival cells, and disturbing MGs 18,29 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…First, the lack of a standardized test orientated to evaluate filtering bleb dysesthesia. Second, there was a high prevalence of dry eye among the glaucoma-operated patients even with functioning blebs [45] . Our study shows low values on the OSDI scale.…”
Section: Discussionmentioning
confidence: 99%